Advanced design strategies for Fe-based metal-organic framework-derived electrocatalysts toward high-performance Zn-air batteries - Guo, Ya-Fei; Zhao, Shan; Zhang, Nan; Liu, Zong-Lin; Wang, Peng-Fei; Zhang, Jun-Hong; Xie, Ying; Yi, Ting-Feng (Energy & environmental science, 2024)
Zinc-air batteries (ZABs) are considered as one of the most promising energy systems due to their environmentally friendly and high energy density characteristics. Nevertheless, the kinetics of oxygen reaction at the air electrode of ZABs are slow, resulting in poor energy efficiency and cycling properties of ZABs. How to improve the overall performance and long-term cycling stability of ZABs is the key to their development. So far, precious metals and their alloys have been considered the most ideal oxygen reduction reaction/oxygen evolution reaction catalysts. Nevertheless, the high cost and low storage capacity of these precious metals limit their application. Transition metal catalysts have received widespread attention because of their high electrocatalytic activity, structural stability, abundant reserves, and low prices. Among them, Fe-based catalysts are regarded as one of the most hopeful candidates due to their lowest price and ease of performance improvement. Metal-organic frameworks (MOFs) have advantages such as structural diversity, high specific surface area (SSA), and porosity. Especially as precursors of transition metal catalysts, organic ligands in MOFs are combined with bridged metal nodes to provide the necessary metals, carbon, and heteroatoms for electrocatalysts. However, MOFs may experience structural collapse, atomic aggregation, and reduced active sites during pyrolysis, which limits their commercial applications. Therefore, nano-design is extremely significant in improving catalytic capability. This review summarizes the morphology, composition, and structural control strategies of Fe-based MOF-derived electrocatalysts. In addition, the active sites, catalytic mechanism, and corresponding characteristics of electrocatalysts are introduced. Finally, the challenges and development prospects of optimized oxygen electrocatalysts in ZABs are discussed. This review provides insights into the targeted optimization of Fe-based MOF derived oxygen electrocatalysts and is expected to promote the future development of high-performance ZABs. This article summarizes the regulation strategies of Fe-based MOFs-derived electrocatalysts for ZABs, and provides a prospect for their future development.